(untitled) (Scientific journal of the Fergana State University, 2025)
The article defines the theoretical foundations for shaping the structure and components of developing a culture of healthy lifestyle in future physical education teachers. It identifies pedagogical methods for shaping the pedagogical competence of future physical education teachers in promoting a healthy lifestyle, examines the effectiveness of methods for developing pedagogical competence through practical experience, and outlines the tasks for applying scientific and practical recommendations to practice.